No cross-sectional evidence for an increased relation of cognitive and sensory abilities in old age1. (3rd April 2017) - Ihle, Andreas; Oris, Michel; Fagot, Delphine; Kliegel, Matthias
Abstract : Objectives: A key question in gerontological research concerns whether good functioning can be maintained in some cognitive abilities in old age, even if deficits occur in other cognitive or sensory abilities. Our goals were to investigate relations of cognitive and sensory abilities in old age, whether these relations differed in size across old age, and whether this was affected by general cognitive ability (processing speed), educational level, and/or general health status. Methods: Two thousand eight hundred and twelve older adults (aged 65–101, M = 77.9 years) from the Vivre–Leben–Vivere survey served as cross-sectional sample for the present study. We administered psychometric tests on processing speed (the speed of cognitive processing), cognitive flexibility (the ability to alternate between cognitive operations), and verbal abilities (vocabulary). In addition, we interviewed individuals on their hearing, eyesight, educational level, and general health status. We regressed sizes of relations between abilities (calculated within each 1-year age tranche) on mean age within the corresponding age tranche, with the number of participants within the corresponding age tranche as case weights. Results: We observed a decrease in relations between processing speed and cognitive flexibility in old age that was particularly pronounced in individuals with high educational level ( r = −.41). In contrast, we did not find differences in relations between other cognitive and sensory abilities across old age, which held for different levels of general cognitive ability, education, and general health status. Conclusion: Present data do not support the view of a generally increased relation of cognitive and sensory abilities in old age.